‘Race the Wild’: Encountering Non-human Life Through the Gamification of Wildlife Movement - Chris Sandbrook; Emma Tait; William M. Adams (Conservation & Society)
Digital technologies are becoming increasingly important in human engagements with the natural world. It has been suggested that digital games could contribute to the work of biodiversity conservation organisations, mediating human understanding of, and responses to, living nature. In this paper, we explore the implications of enrolling non-human nature into conservation gaming projects, focusing on the example of gamifying animal movement data. We discuss a simple experiment where people ‘race’ against animals in an exercise app, examining how wild animals are represented in digital games through digital technologies. We also explore how tracking technologies make animals digital, and how these digital animals can be central to gaming experiences. We consider what is involved in these transitions and enrolments of wild animals into gaming environments, and explore a series of issues that seem to us to deserve further thought and discussion: what humans can learn from games featuring non-human animals; whether games evoke empathy for the non-humans; whether games allow a human player to learn about the political ecology of landscapes within which wild animals exist; questions of ethics and power associated with the involuntary enrolment of animals into the gamification dynamic; the commodification involved in ‘animal games’; and the carbon and other impacts of ‘games for nature’. Digital games are a global phenomenon and a global industry. Their role in the lived experience of being human continues to expand. We suggest that there is value in conservationists and those who analyse and critique the political ecologies of conservation thinking further about digital games, digital animals and digital natures.